Evaluation of User Experience (UX) in the MIUI 14 Interface Using User Experience Questionnaire (UEQ) Method in Indonesia - Diana Khuntari; Aradhea Rizky Danusessia; Arum Marwati (Journal of Information Technology and Its Utilization, 2025)
The advancement of the modern era has provided various boosts and innovations for smartphone development companies worldwide. This development has led smartphone manufacturers to compete in creating their own Android-based user interfaces. MIUI, a widely recognized interface due to its popularity, still has several shortcomings in delivering a good user experience, such as overheating issues, UI lag, battery drain, bloatware, promotional ads, GPS issues, OS & security updates, and conflicts between Xiaomi China and Google. This study aims to assess user experience in terms of attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty as offered by the MIUI 14 interface. A descriptive quantitative approach is used in this study, employing a questionnaire as the data collection method. The questionnaire, consisting of a series of written questions, was distributed to respondents for their answers. This method is particularly effective when the number of respondents is large and geographically spread out. The questionnaire is designed to assess user experience with MIUI 14 according to the indicators in the User Experience Questionnaire (UEQ) method. Data analysis was carried out using specialized software for user experience measurement, specifically the UEQ tool. The results show that the UEQ dimensions of attractiveness, perspicuity, and dependability received positive impressions, while efficiency received a negative impression. Stimulation and novelty received neutral evaluations. MIUI 14 scored Above Average in attractiveness, Below Average in perspicuity and dependability, and Poor in efficiency, stimulation, and novelty. Suggested improvements include addressing advertising notifications, rearranging the settings layout, enhancing animation responsiveness, removing bloatware, updating security patches, and implementing the Material You design concept.